Production of antibiotic resistance gene-free urease-deficient recombinant BCG that secretes antigenic protein applicable for practical use in tuberculosis vaccination. (July 2021) - Miyamoto, Yuji; Tsukamoto, Yumiko; Maeda, Yumi; Tamura, Toshiki; Mukai, Tetsu; Ato, Manabu; Makino, Masahiko
Abstract: Mycobacterium bovis BCG has been the only practical vaccine for tuberculosis. However, BCG cannot fully prevent adult pulmonary tuberculosis. Therefore, the improvement of BCG vaccine is necessary. We previously produced recombinant (r) BCG (BCG-PEST) for the better control of tuberculosis. BCG-PEST was developed by introducing PEST-Heat Shock Protein (HSP)70-Major Membrane Protein (MMP)–II–PEST fusion gene into urease-deficient rBCG using antibiotic-resistant gene for the selection of rBCG. HSP70-MMPII fusion protein is highly immunogenic and PEST sequence was added to enhance processing of the fusion protein. Although BCG-PEST effectively inhibited intrapulmonary growth of Mycobacterium tuberculosis (MTB), BCG with antibiotic-resistant gene is not appropriate for human use. Therefore, we produced antibiotic-resistant gene-free rBCG. We generated leucine-biosynthetic gene (leuD )-deficient BCG and introduced the fusion gene with leuD as the selection marker and named this rBCG as BCG-LeuPH. BCG-LeuPH activated human naïve T cells of both CD4 and CD8 subsets and efficiently inhibited aerosol-challenged MTB in mice. These results indicate that leuD can replace antibiotic-resistant gene for the selection of vaccine candidates of rBCG for human use.